Addition of lignin to lime materials for expedited pH increase and improved vertical mobility of lime in no‐till soils. (8th May 2019) - Tao, Haiying; Pan, William L.; Carter, Paul; Wang, Ku
Abstract: Soil acidification caused by long‐term nitrogen (N) fertilizer applications has been a growing concern for dryland crop production in both tilled and no‐till soils in the Pacific Northwest (PNW). Many no‐till soils have stratified soil pH in the 5–10 cm depth due to repeated N fertilizer applications at this depth. In the PNW, the practice of liming to correct low soil pH is complicated due to lack of affordable lime sources and because the inherent difficulty in ameliorating stratified soil acidity in no‐till systems. An intact soil‐column incubation study was conducted to investigate whether mixing lime materials with lignin‐containing black liquor—a by‐product from the pulp industry—could elevate soil pH change in both conventional and no‐till systems and expedite vertical downward movement of lime in no‐till system. Results indicate that mixing lime with black liquor has the potential to not only elevate the increase in soil pH in both conventional till and no‐till systems, but also accelerate downward movement of lime to correct soil pH below the soil surface. Mixing agricultural lime or super fine micro lime with black liquor increased soil pH to a depth of 25–30 cm within 147 days after surface application to a no‐till soil.